AKSESIBILITAS PEJALAN KAKI DI STASIUN YANG TERINTEGRASI DENGAN RENCANA TERHADAP KAWASAN BERKONSEP TOD (STUDI KASUS KAWASAN STASIUN TANJUNG BARAT) - Gading Kencono Aji; Sylvira Ananda; Tri Mulyono (Menara: Jurnal Teknik Sipil, 2019)
This research was conducted to assess the Level Of Service (LOS) pedestrian path around the Tanjung Barat Station area. In addition, to see in terms of comfort and security in reaching a TOD concept area. For this reason, a model of pedestrian design is needed so that track users can enjoy the pedestrian pathway feeling comfortable and safe. The results of this study indicate that the level of pedestrian service on the Tanjung Barat Raya road and on the road in Lenteng Agung raya: For the Tanjung Barat Raya road the LOS index is categorized as "B" while the Lenteng Agung Raya road is in the LOS index in the "C" category. And for the prediction of the next 5 years, LOS is categorized as "B". This indicates the need for improvements in terms of supporting facilities for pedestrians on the two St. Western Cape. This indicates that the pedestrian support facilities need to be improved which will have an impact on the increasing number of pedestrian users around the West Tanjung station for the next 5 years.